2020
DOI: 10.1097/lbr.0000000000000740
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biopsy Tool Choice and Rapid On-Site Evaluation on Diagnostic Accuracy for Malignant Lesions in the Prospective

Abstract: Background: The diagnostic yield of electromagnetic navigation bronchoscopy (ENB) is impacted by biopsy tool strategy and rapid on-site evaluation (ROSE) use. This analysis evaluates usage patterns, accuracy, and safety of tool strategy and ROSE in a multicenter study. Methods: NAVIGATE (NCT02410837) evaluates ENB using the superDimension navigation system (versions 6.3 to 7.1). The 1-year analysis included 1215 prospectively enrolled subjects at 29 United States sites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…While a recent study reported lesion localization of 97% [ 4 ], diagnostic yields remain lower at 83% [ 5 ]. This is likely multifactorial; however, it suggests that despite reaching the lesion with the bronchoscope, biopsy tool strategies are ineffective at acquiring targeted tissue, especially with extraluminal lesions adjacent to the airway [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a recent study reported lesion localization of 97% [ 4 ], diagnostic yields remain lower at 83% [ 5 ]. This is likely multifactorial; however, it suggests that despite reaching the lesion with the bronchoscope, biopsy tool strategies are ineffective at acquiring targeted tissue, especially with extraluminal lesions adjacent to the airway [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NAVIGATE post hoc analysis confirmed that in the multimodal approach strategy to the nodule, the aspirating needle and forceps had higher true-positive rates [ 6 , 25 ]. The Acquire registry reported that TBNA improved diagnostic yield when compared with other diagnostic tools, such as forceps biopsy, transbronchial brushing and lavage [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the possible benefits, even in expert centers, TBNA is underused in real-world practice [ 15 , 16 , 23 ]. Similarly, for ENB, transbronchial forceps biopsy remains the mainstream modality for tissue sampling followed by needle aspiration [ 14 , 24 , 25 ]. Several studies have suggested a higher diagnostic yield with ENB-guided TBNA than forceps biopsy, while few studies have suggested that using multiple tools may be more effective than single-tool strategies [ 11 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated in order to determine a 15% difference in the diagnostic yield between the individual modalities and their combined use owing to the expected better and synergistic diagnostic yield. The estimated difference in the diagnostic yield (67% vs. 82%) is based on previously conducted large-scaled observational studies and meta-analyses that suggested an improved diagnostic yield with the use of needle aspiration and a combination of both modalities [ 11 , 12 , 14 , 16 ]. The calculation was based on this difference in the diagnostic accuracy for equality of paired proportions with a two-sided significance level of 0.05 and 80% power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation